Perkembangan Identitas Sosial dan Implikasinya dalam Konseling Multibudaya - Muhammad Syaiful Muiz; Kinanti Tria Sekar Putri; Elvina Khoirun Nisa Qismutawabih; Eva Nabila; Rani Ditia Ningsih; Chandra Duwita Ela Pradana (FKIP Universitas Islam Jember, 2026)
Cultural diversity requires counselors to have multicultural competence so that guidance and counseling services can be carried out effectively and fairly. This study aims to examine the nature of multicultural counseling, the concepts of culture and culture, and their implications in counseling practice. The method used in this study is descriptive qualitative through a literature study approach, which analyzes books, journal articles, and scientific sources relevant to the topic of multicultural counseling. The results of this study show that culture and cultural practices play an important role in shaping the behavior, values, and perspectives of counselees. Multicultural counseling emphasizes counselor competencies that include multicultural awareness, multicultural knowledge, and multicultural skills to prevent cultural bias that can lead to misunderstandings in counseling sessions. The application of the principles of cultural relativism and a non-discriminatory attitude has proven to be important in building an empathetic and inclusive counseling relationship. Multicultural counseling is an essential approach in providing guidance and counseling services that are responsive to cultural diversity, especially in the context of Indonesia's multicultural society.